"But I want to talk to you!" Perspectives on music therapy practice with highly verbal children on the autism spectrum. Issue 4 (8th August 2019) - Thompson, Grace Anne; Elefant, Cochavit
ABSTRACT: Introduction : This reflective paper offers a perspective on music therapy practice that explores how shared music experiences may provide opportunities for highly verbal children on the autism spectrum to expand their engagement in social play. Methods : Relevant literature from the fields of music therapy, child development, and the neurodiversity movement are discussed alongside the authors' reflections on their work with children who bring verbal and gestural motifs into music therapy sessions. The case examples highlight moments where the music therapist transformed the child's verbal and gestural material into interactive music-based games. Results : This paper proposes practice considerations for music therapists working with highly verbal children that centre around the therapist's intention to support the child to interact with freedom and joy through musical play and foster relationships with others. These intersubjective moments within creative musical play experiences may create conditions for the child to explore different ways of being, interacting and communicating. Discussion : Musical games within the context of music therapy emphasise the relational value of a mutually created and shared world of meaning between the therapist and the child. The child's verbal strengths are not simply acknowledged; they become the foundation for musical-play experiences that aim to expand their repertoire of social and relational experiences.